Electronic structure of Gd based transition metal antimonides GdTSb (T = Ni, Pt) - Sahariya, Jagrati; Kumar, Pancham; Bhamu, K. C.; Soni, Amit (2nd International Conference on Condensed Matter and Applied Physics (ICC-2017), 2018)
We report the electronic and magnetic properties of ternary GdNiSb and GdPtSb compounds with cubic MgAgAs type structure. The energy bands, density of states and atom specific magnetic moments of compounds have been computed using GGA+U approach. The calculations predict that GdNiSb is a small band gap semiconductor whereas GdPtSb is metallic in nature.

Opto-electronic analysis of Cs2PdCl2Br4 Perovskites compounds for photovoltaic applications - Soni, Amit; Sahariya, Jagrati; Bhamu, K. C.; Ahuja, Ushma (2018 International Conference and Utility Exhibition on Green Energy for Sustainable Development (ICUE), 2018)
In this paper, electronic and optical properties of Cs2PdCl2Br4 perovskite compound are presented using full potential linearized augmented plane wave (FP-LAPW) method. All computations are performed using most accurate modified Becke Johnson (mBJ) potential within density functional theory. Energy band computations are performed over here to elaborate relationship between energy and wave vector (k). Pattern of occurrence observed for energy bands are analyzed in terms of plotted total and partial density of states. For investigating optical behavior of Cs2PdCl2Br4, we have computed dielectric tensor, absorption spectra, reflectivity and refraction spectra using mBJ potential. Different peaks recorded in the imaginary components of dielectric tensor are interpreted in terms of interband transitions for better understanding. Significant absorption intensity available in desired energy range and suitable band gap indicates effective utilization of this compound in photovoltaic applications.

Opto-electronic analysis of promising photovoltaic Cs2PdCl4Br2: An upcoming perovskite material - Sahariya, J.; Soni, A.; Bhamu, K. C. (WIECON-ECE 2017 - IEEE International WIE Conference on Electrical and Computer Engineering 2017, 2018)
he metal halide perovskites are attracting much attention due to their potential applications in optoelectronic devices. Herein, we review and calculate a new avenue for Cs 2 PdCl 4 Br 2 perovskites by computing its electronic and optical properties to show its candidature in optoelectronics. For the computation of electronic and optical properties, we have used modified Becke Johnson approximation available in Wien2k code, based on full potential linearised augmented plane wave method. Investigated electronic and optical properties show that Cs 2 PdCl 4 Br 2 has the indirect band gap of 1.70 eV. The significant intense peaks in absorption spectra between energy range 2-3 eV reveals the utility of this compound in solar cells and other optoelectronic devices.

Revealing optoelectronic and transport properties of potential perovskites Cs2PdX6 (X = Cl, Br): A probe from density functional theory (DFT) - Bhamu, K. C.; Soni, Amit; Sahariya, Jagrati (Solar Energy, 2018)
Metal-halide perovskites are rapidly emerging crystalline materials that are reasonably preferred as leading aspirant for applications in optoelectronic and thermoelectric devices. In this paper, we have thoroughly reviewed and performed calculations to reveal optoelectronic and transport properties for a potential newcomer, Cs2PdX6 (X = Cl, Br) termed as Cesium Palladium Halides (CPH). Outcome of present computations are compared with available results and a reasonable agreement is recorded. Energy band gap computations performed reveal indirect band gap of 2.29 eV for Cs2PdC16, which substantially reduces to 1.22 eV when `Cl' is replaced by `Br'. Optical absorption spectra investigations performed here, in the energy range from 3 to 5 eV confirms effective utilization of these compounds in solar cells and other optoelectronic applications. In addition, the transport properties computations performed using semi-classical Boltzmann theory, shows constant pattern of thereto power near ambient temperature range (200-500 K), which admits possible utilization of these compounds as low temperature thermoelectric materials. Performed ZT calculations demonstrates reasonably good thermoelectric performance for both materials, as there exist minor variation (0.1) in the values over wide temperature ranges i.e. from 100 to 800 K. Further, detailed analysis of transport properties predicts p-type semiconducting nature of the present series of materials.
Keywords: Ab-initio studies; Density functional theory; Optical properties; Transport properties

Spatial-temporal spectroscopy characterizations and electronic structure of methylammonium perovskites - Liu, Zhaoyu; Bhamu, K. C.; Luo, Liang; Shah, Satvik; Park, Joong-Mok; Cheng, Di; Long, Men; Biswas, Rana; Fungara, F.; Shiner, Ruth; Shiner, Joseph; Vela, Javier; et al. (MRS Communications, 2018)
Using time-resolved laser-scanning confocal microscopy and ultrafast optical pump/THz probe spectroscopy, we measure photoluminescence (PL) and THz-conductivity in perovskite micro-crystals and films. PL quenching and lifetime variations occur from local heterogeneity. Ultrafast THz-spectra measure sharp quantum transitions from excitonic Rydberg states, providing weakly bound excitons with a binding energy of similar to 13.5 meV at low temperatures. Ab-initio electronic structure calculations give a direct band gap of 1.64 eV, a dielectric constant of similar to 18, heavy electrons, and light holes, resulting in weakly bound excitons, consistent with the binding energies from the experiment. The complementary spectroscopy and simulations reveal fundamental insights into perovskite light-matter interactions.

Temperature and pressure dependent thermodynamic behavior of 2H-CuInO2 - Bhamu, K. C. (AIP Conference Proceedings, 2018)
Density functional theory and quasi-harmonic Debye model has been used to study the thermodynamic properties of 2H-CuInO2. At the optimized structural parameters, pressure (0 to 80 GPa) dependent variation in the various thermodynamic properties, i.e. unit cell volume (V), bulk modulus (B), specific heat (Cv), Debye temperature (ӨD), Grǘneisen parameter (γ) and thermal expansion coefficient (α) are calculated for various temperature values. The results predict that the pressure has significant effect on unit cell volume and bulk modulus while the temperature shows negligible effect on both parameters. With increasing temperature thermal expansion coefficient increase while with increasing pressure it decreases. The specific heat remains close to zero for ambient pressure and temperature values and it increases with increasing temperature. It is observed that the pressure has high impact on Debye temperature and Grǘneisen parameter instead of temperature. Debye temperature and Grǘneisen parameter both remains almost constant for the temperature range (0-300K) while Grǘneisen parameter decrease with increasing pressure at constant temperature and Debye temperature increases rapidly with increasing pressure. An increase in Debye temperature with respect to pressure shows that the thermal vibration frequency changes rapidly.

Investigating effect of strain on electronic and optical properties of lead free double perovskite Cs2AgInCl6 solar cell compound: A first principle calculation - Soni, Amit; Bhamu, K. C.; Sahariya, Jagrati (Journal of Alloys and Compounds, 2020)
Despite serious problems associated with toxicity of lead, lead halide perovskite based solar cells have resulted with remarkable efficiency and hence gained much interest. To overcome this aspect, numerous solutions are attempted by researchers which include the development of new environmental friendly lead free double perovskite (DP) photovoltaic materials. Enlightening on the same line, we report first principle calculations on electronic and optical properties of Cs2AgInCl6 solar photovoltaic materials. Present opto-electronic computations for lead free DP compound, have been performed using the full potential linearized augmented plane wave method. In present investigations, we have adopted exchange and correlation potentials prescribed by Perdew et al. and the most accurate Tran-Blaha modified Becke-Johnson. Both exchange and correlation potential computations are performed with and without spin orbit coupling. Results obtained for electronic and optical properties are validated by systematic comparison with available experimental data. Reasonable reconciliation between investigated results and the available experimental data, endorse accuracy of present computations. To identify the effect of strain on energy gap and hence on the optical properties of Cs2AgInCl6 compound, computations of electronic and optical properties have also been performed under the different values of strain application. (C) 2019 Elsevier B.V. All rights reserved.
Keywords: Density functional theory; Electronic Structure; Optical properties; solar cells

Density functional theory-based study of the magnetic and optical properties of PbMO3 (M = Cr, Fe) using the modified BeckeJohnson mBJ functional (vol 128, pg 275, 2019) - Mahmood, Q.; Hassan, M.; Bhamu, K. C.; Yaseen, M.; Ramay, S. M.; Mahmood, A. (Journal of Physics and Chemistry of Solids, 2021)

Electronic and optical properties of vacancy ordered double perovskites A(2)BX(6) (A=Rb, Cs; B=Sn, Pd, Pt; and X=Cl, Br, I): a first principles study - Faizan, Muhammad; Bhamu, K. C.; Murtaza, Ghulam; He, Xin; Kulhari, Neeraj; AL-Anazy, Murefah Mana; Khan, Shah Haidar (Scientific Reports, 2021)
The highly successful PBE functional and the modified Becke-Johnson exchange potential were used to calculate the structural, electronic, and optical properties of the vacancy-ordered double perovskites A(2)BX(6) (A=Rb, Cs; B=Sn, Pd, Pt; X=Cl, Br, and I) using the density functional theory, a first principles approach. The convex hull approach was used to check the thermodynamic stability of the compounds. The calculated parameters (lattice constants, band gap, and bond lengths) are in tune with the available experimental and theoretical results. The compounds, Rb2PdBr6 and Cs2PtI6, exhibit band gaps within the optimal range of 0.9-1.6 eV, required for the single-junction photovoltaic applications. The photovoltaic efficiency of the studied materials was assessed using the spectroscopic-limited-maximum-efficiency (SLME) metric as well as the optical properties. The ideal band gap, high dielectric constants, and optimum light absorption of these perovskites make them suitable for high performance single and multi-junction perovskite solar cells.

Improving the optical and thermoelectric properties of Cs2InAgCl6 with heavy substitutional doping: a DFT insight - Bhamu, K. C.; Haque, Enamul; Praveen, C. S.; Kumar, Nandha; Yumnam, G.; Hossain, Md. Anwar; Sharma, Gautam (RSC Advances, 2021)
The next-generation indium-based lead-free halide material Cs2InAgCl6 is promising for photovoltaic applications due to its good air stability and non-toxic behavior. However, its wide bandgap (>3 eV) is not suitable for the solar spectrum and hence reduces its photoelectronic efficiency for device applications. Here we report a significant bandgap reduction from 2.85 eV to 0.65 eV via substitutional doping and its effects on the optoelectronic and opto-thermoelectric properties from a first-principles study. The results predict that Sn/Pb and Ga and Cu co-doping will enhance the density of states significantly near the valence band maximum (VBM) and thus reduce the bandgap via shifting the VBM upward, while alkali metals (K/Rb) slightly increase the bandgap. A strong absorption peak near the Shockley-Queisser limit is observed in the co-doped case, while in the Sn/Pb-doped case, we notice a peak in the middle of the visible region of the solar spectrum. The nature of the bandgap is indirect with Cu-Ga/Pb/Sn doping, and a significant reduction in the bandgap, from 2.85 eV to 0.65 eV, is observed in the case of Ga-Cu co-doping. We observe a significant increase in the power factor (PF) (2.03 mW m(-1) K-2) for the n-type carrier after Pb-doping, which is similar to 3.5 times higher than in the pristine case (0.6 mW m (-1) K-2) at 500 K.